Novel Approach for the Approximation of Vitamin D3 Pharmacokinetics from In Vivo Absorption Studies - Grzegorz Żurek; Magdalena Przybyło; Wojciech Witkiewicz; Marek Langner (MDPI AG, 2023)
The changing environment and modified lifestyles have meant that many vitamins and minerals are deficient in a significant portion of the human population. Therefore, supplementation is a viable nutritional approach, which helps to maintain health and well-being. The supplementation efficiency of a highly hydrophobic compound such as cholecalciferol (logP > 7) depends predominantly on the formulation. To overcome difficulties associated with the evaluation of pharmacokinetics of cholecalciferol, a method based on the short time absorption data in the clinical study and physiologically based mathematical modeling is proposed. The method was used to compare pharmacokinetics of liposomal and oily formulations of vitamin D3. The liposomal formulation was more effective in elevating calcidiol concentration in serum. The determined AUC value for liposomal vitamin D3 formulation was four times bigger than that for the oily formulation.